2022
DOI: 10.24843/jkb.2022.v12.i02.p05
|View full text |Cite
|
Sign up to set email alerts
|

Konservasi Burung di Hutan Adat: Refleksi Kritis Mahasiswa Belajar dari Kearifan Lokal Desa Demulih Bangli

Abstract: This paper focuses on undergraduate students’ critical reflection in a service-learning (S-L) project to promote the conservation of the birds based on local wisdom in a village in Bali. The students are working in a partnership with researchers and local communities from a traditional rural village, namely Desa Adat Demulih, Bangli regency. The objective of this paper is to show what students can learn and how they gain personal growth, civic-learning and academic enhancement during the S-L project. The findi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Local wisdom like this is a biocultural diversity that needs to be integrated into biology learning so that biological concepts or materials are in real-life contexts (Bürgi & Kizos, 2015;Deveci & Karteri, 2022). This research indicates that the distribution and mythology of AHH around HABD provide a perspective on the urgency of an ecological-social approach in biology learning, which can not only support learning targets but also potentially provide benefits to society, especially related to community-based wildlife conservation efforts (Cocks et al, 2012;McRuer & Zethelius, 2017;Surata et al, 2022).…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Local wisdom like this is a biocultural diversity that needs to be integrated into biology learning so that biological concepts or materials are in real-life contexts (Bürgi & Kizos, 2015;Deveci & Karteri, 2022). This research indicates that the distribution and mythology of AHH around HABD provide a perspective on the urgency of an ecological-social approach in biology learning, which can not only support learning targets but also potentially provide benefits to society, especially related to community-based wildlife conservation efforts (Cocks et al, 2012;McRuer & Zethelius, 2017;Surata et al, 2022).…”
Section: Discussionmentioning
confidence: 85%
“…Previous research shows that the forest is rich in bird diversity, including AHH (Sulistyobudi, 2021). The presence of various birdlife in HABD has been the focus of collaborative research between students, lecturers, and village partners in promoting HABD as a bird conservation area (Surata et al, 2022). Both studies found AHH widespread in almost all areas due to favorable habitat factors and the community's belief that AHH are sacred animals protected by the community (Sulistyobudi, 2021;Surata dkk., 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Banana leaves in the cultural tradition of the Balinese people, young leaves to dry leaves, are used in Hindu religious rituals and as wrappers for traditional snacks [3].…”
Section: Introductionmentioning
confidence: 99%